2001
DOI: 10.1006/jcis.2001.7875
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Estimation for Counterion Dissociation of Cationic Micelles Using Chloride-Sensitive Fluorescence Probe

Abstract: The concentration dependent properties exhibit a break point due to the micellization.The CMC of surfactant is usually determined by plotting those properties as a function of concentration. The other important property of ionic surfactant solutions is the degree of micellar counterion dissociation, which has been used to be quantified by the two-site model (7,8). From this simple model one can calculate the α by using the concentrations of "free" ions in the aqueous bulk phase and "bound" ions in micellar pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 18 publications
18
68
0
Order By: Relevance
“…Hence, degree of association (α =(1−g)) decreases. The degree of dissociation (g) decreases with increase in electrolyte concentration [39] and may decrease with micellar growth [40]. Also, with the increase…”
Section: Degree Of Dissociation In Absence and Presence Of Salt (G)mentioning
confidence: 98%
“…Hence, degree of association (α =(1−g)) decreases. The degree of dissociation (g) decreases with increase in electrolyte concentration [39] and may decrease with micellar growth [40]. Also, with the increase…”
Section: Degree Of Dissociation In Absence and Presence Of Salt (G)mentioning
confidence: 98%
“…From Table 1, it is clear that alkyltrimethylammonium compounds (ATMAC) and DADMACs, show correlations exist between increasing hydrophobicity and decreasing critical micelle concentration. Table 1 also illustrates that data on CMC are incomplete and incoherent between authors as experimental setups vary (Asakawa et al 2001;Lemić et al 2005;Marcotte et al 2005;Diress et al 2007;Cepeda et al 2013). Several studies have reported calculated values for the octanol-water partition coefficient for QAACs, although, these are not valid due to the surfactant nature of this compound class.…”
Section: Structures and Properties Of Qaacsmentioning
confidence: 99%
“…The anionic surface active agents: sodium dodecyl sulfate (Laurylsulfate, LS) (critical micellar concentration in water, cmc ¼ 7.4 mM [27]), sodium decylsulfate (DS) (cmc ¼ 33 mM [28]), with the same hydrophobic group but shorter aliphatic chain length, and sodium dodecylsulfonate (DD), with 12 carbon atoms in the hydrophobic chain but a different polar group, were obtained from Sigma (Spain). The cationic surfactants: N-cetyl-trimethyl ammonium chloride (CTAC) (cmc ¼ 1.31 mM [29]), N-decyl-trimethylammonium chloride (DTAC) (cmc ¼ 24.4 mM [29]) and dodecylpirydinium chloride (DP) (cmc ¼ 16.8 mM [30]) were purchased from Merck (Spain). These compounds were used for the study of the electrochemistry of acidic catecholamine metabolites.…”
Section: Reagents and Proceduresmentioning
confidence: 99%